Increased abundance of bacteria of the family Muribaculaceae achieved by fecal microbiome transplantation correlates with the inhibition of kidney calcium oxalate stone deposition in experimental rats - Wang, Yan; Sun, JinBo; Xie, Sen; Zhou, Yu; Wang, Tao; Liu, ZhenYu; Li, ChaoSheng; Gao, Lei; Pan, TieJun (Frontiers in Cellular and Infection Microbiology, 2023)
Background: The incidence of nephrolithiasis is increasing rapidly worldwide. As the major constituent, calcium oxalate contributes to about 80% of all kidney stones. Gut microbiome may play a role in decreasing the morbidity of urinary calculus with oxalate-degrading ability. Fecal Microbiome Transplantation (FMT) has been reported to be an effective treatment for the restoration of the gastrointestinal microbial community in different conditions. The utilization of whole communities adapted to oxalate degradation may be a more effective strategy for transferring oxalate-degrading function than isolated strains. Methods: The Fecal Microbiome Transplantation was carried out in male guinea pigs and male Sprague-Dawley laboratory rats (SDR). Fresh feces were collected from guinea pigs through metabolic cages. Sprague-Dawley rats were divided into 4 groups, group SC and SC+FMT received standard rat chow (SC), group OD+PBS and OD+FMT were fed with 5% potassium oxalate diet (OD). On 14th day, group OD+PBS, OD+FMT and SC+FMT received esophageal gavage of PBS or guinea pigs feces respectively. The microbiota composition of guinea pigs and Sprague-Dawley rats was analyzed through 16S rRNA gene sequencing approach. The urinary and serum biochemistry as well as kidney CaOx crystal of Sprague-Dawley rats were detected. Renal function was examined by using Real-Time PCR analysis and immunohistochemistry staining for renin, ACE and OPN expression. Results: Fecal Microbiome Transplantation resulted in a gut microbiota that was a mixture of Guinea Pigs and SDR bacteria. Increased relative abundance of oxalate-degrading bacteria such as Muribaculaceae, Lactobacillus and Bifidobacterium in group OD+FMT owing to Fecal Microbiome Transplantation, caused significant reduction of urinary oxalate, calcium, uric acid, creatinine, urea and serum uric acid, BUN/creatinine ratio (P<0.05). Microscopic observations revealed a high score (4+) of CaOx crystal in kidneys of group OD+PBS, whereas a lower score (2+) was observed in group OD+FMT. Up-regulation of OPN and down-regulation of renin was also connected with Fecal Microbiome Transplantation. Conclusion: Increased relative abundance of Muribaculaceae and other oxalate-degrading bacteria by Fecal Microbiome Transplantation was capble of reducing urinary oxalate excretion and CaOx crystal deposition in kidney by increased intestinal oxalate degradation. Fecal Microbiome Transplantation may exert a renoprotective function in oxalate-related kidney stone.